Jewish honor courts : revenge, retribution, and reconciliation in Europe and Israel after the Holocaust - Jockusch, Laura HerausgeberIn; Finder, Gabriel N. HerausgeberIn; United States Holocaust Memorial Museum (Wayne State University Press, 2015)
In the aftermath of World War II, virtually all European countries struggled with the dilemma of citizens who had collaborated with Nazi occupiers. Jewish communities in particular faced the difficult task of confronting collaborators among their own ranks--those who had served on Jewish councils, worked as ghetto police, or acted as informants. European Jews established their own tribunals--honor courts--for dealing with these crimes, while Israel held dozens of court cases against alleged collaborators under a law passed two years after its founding. In Jewish Honor Courts: Revenge, Retribution, and Reconciliation in Europe and Israel after the Holocaust, editors Laura Jockusch and Gabriel N. Finder bring together scholars of Jewish social, cultural, political, and legal history to examine this little-studied and fascinating postwar chapter of Jewish history.--Provided by publisher